De Comenius a Freire: uma revisão bibliográfica da evolução da didática para os anos iniciais do ensino fundamental na BNCC - Messiano, Paola Aparecida Ferreira (Universidade Federal de São Carlos, 2025)
This paper revisits classical didactic theories with the aim of understanding their influence on current educational practices, particularly in the context of the Brazilian National Common Curricular Base (BNCC) and Primary Education. The research analyzes the contributions of historical educators such as Comenius, Rousseau, Dewey, the new school movement, and Paulo Freire, exploring the applicability of their ideas in the contemporary educational landscape. Although the BNCC primarily focuses on technical and curricular aspects, the study proposes a critical reflection on the integration of classical pedagogical theories within the Brazilian educational system. By emphasizing the importance of grounding pedagogical practices in solid theoretical foundations, the research suggests that the ideas of classical didactics continue to provide relevant theoretical support for promoting a more critical, reflective, and transformative education. Finally, the paper invites education professionals to reconsider their practices, seeking a balance between theoretical traditions and contemporary demands.
From Comenius to Freire: a literature review of the evolution of teaching methods for the early years of elementary school in the BNCC
Keywords: Didática; Base Nacional Comum Curricular; Clássicos da didática; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; 4. Educação de Qualidade